Associação entre o índice de pressão tornozelo-braço e as alterações do metabolismo mineral e microinflamação em hemodiálise - Miguel, Jair Baptista (2006)
Background: Reduced values of ankle-arm index (AAI) have been shown to predict cardiovascular disease and mortality in patients with chronic kidney disease. Objective: To test the hypothesis that changes in AAI could be associated with mineral metabolism disturbances, microinflammation and generalized atherosclerotic disease in hemodialysis patients. Methods: Cross-sectional analysis to evaluate the relationship between the AAI and demographic, clinical and laboratory data, including high-sensitivity C reactive protein (CRP) by the time AAI was measured. Retrospective analysis to evaluate if previous exposure to mineral metabolism disturbances could have influenced the AAI by testing the association between the AAI and the mean values of calcium, phosphorus and parathyroid hormone (PTH) along dialysis treatment. The measures of systolic pressure in the ankle and the arm to obtain AAI were done before hemodialysis session, using hand-held doppler and a standard mercury manometer. Results: A total of 478 patients on regular hemodialysis (3 times a week) for at least 1 year were studied. Fifty-six percent were men, 17% diabetics, and the medians of age and dialysis vintage were 54 (18 to 75) years and 59 (12 to 427) months, respectively. Patients were distributed in terciles according to AAI values (1st tercile AAI <0.97, 2nd tercile AAI between 0.97 to 1.1 and 3rd tercile AAI >1.1). Patients in the lower tercile were older and had a greater prevalence of diabetes, coronary disease, cerebrovascular disease and peripheral arterial disease. There was no difference either in the frequency of hypertension or in dialysis vintage between terciles. Median CRP levels were higher in the 1st tercile. Mean serum calcium was similar in all terciles; mean serum phosphorus was higher in the 3rd tercile; PTH was lower in the 1st tercile. In a logistic regression model, only age, presence of diabetes and elevated CRP were associated with AAI in the lowest tercile, but a trend of association was noticed for low levels of PTH. Conclusions: Hemodialysis patients with AAI < 0.97 were older, with higher prevalence of diabetes and cardiovascular complications. Hypertension and dialysis vintage were not associated with a higher risk of low AAI. The patients with the lowest AAI also had higher values of CRP. There was no correlation between previous cumulative exposure to high levels of calcium and phosphorus and AAI.